Productos forestales no maderables de origen vegetal en cinco comunidades del cantón Zapotillo, provincia de Loja - Rivera Morán, María Esthela (2019)
Non-timber forest products (NTFPs) are important for the well-being of rural communities because their use is a viable alternative for the sustainability of forest management and conservation. The purpose of this research is to identify the main non-timber forest products (NTFPs) of plant origin in five communities of Zapotillo canton, Loja province, in order to know the traditional uses and the possible generational loss of knowledge of use, through the application of semi-structured surveys to the inhabitants of the five communities, finding out about the knowledge and use of plants that provide NTFPs. We worked in 5 communities in the canton (Miraflores, Tronco quemado, Valle hermoso, Jaguay Grande and Ceiba Grande). The number of informants per community was structured according to the population of each community, interviewing 255 people, including men and women, and stratified into age groups that allow us to know the species and their vegetative parts used as NTFPs. The use of 87 species was reported, within 82 genera and 61 families, as well: 31 trees, 38 shrubs and 18 herbs. In terms of age groups, older adults know more about the use of species, due to their relationship with the forest. The best-known categories of NTFPs are: human medicine, fodder, and food and beverages. In Zapotillo's forests, there are NTFPs that the local population knows about their ancestral use, but their use is occasional, which causes a generational loss of knowledge. Of the species identified as NTFPs, the vegetative parts used basically comprise: the root, stem, leaves, flowers, branches, fruits, bark and sometimes the entire plant. The species are managed directly and most grow in forests and open areas. The frequency of exploitation is moderately frequent; the perception of abundance of the plants is average and they are collected in medium quantity. The inhabitants of the community’s state that they collect only the useful part of the plant, mostly for family consumption, rarely for commercialization; the collection is done in dry season because of the ease of access to the ecosystem where the species grow. The knowledge possessed by men and women is similar in the communities studied in Zapotillo canton. Based on the results of traditional uses, frequency of use, and SWOT analysis, technical guidelines were developed to promote NTFP management in the five communities of Zapotillo canton. Two programs are proposed: The second program: Promotion of the use of potential NTFPs through environmentally friendly practices.